2003
DOI: 10.1523/jneurosci.23-08-03325.2003
|View full text |Cite
|
Sign up to set email alerts
|

Role of DE-Cadherin in Neuroblast Proliferation, Neural Morphogenesis, and Axon Tract Formation inDrosophilaLarval Brain Development

Abstract: In the wild-type brain, the Drosophila classic cadherin DE-cadherin is expressed globally by postembryonic neuroblasts and their lineages ("secondary lineages"), as well as glial cells. To address the role of DE-cadherin in the larval brain, we took advantage of the dominant-negative DE-cad(ex) construct, the expression of which was directed to neurons, glial cells, or both. Global expression of DE-cad(ex) driven by a heat pulse during the early second instar resulted in a severe phenotype that included defici… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
137
2
3

Year Published

2005
2005
2012
2012

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 113 publications
(156 citation statements)
references
References 38 publications
(54 reference statements)
5
137
2
3
Order By: Relevance
“…1F,G) (Dumstrei et al, 2003). Dumstrei et al (Dumstrei et al, 2003) showed that global expression of a dominant-negative form of DE-Cadherin driven by a heat pulse during early second instar results in a severe phenotype that includes deficits in neural proliferation: although neuroblasts appears in approximately normal numbers, they have highly reduced mitotic activity.…”
Section: Research Articlementioning
confidence: 99%
See 1 more Smart Citation
“…1F,G) (Dumstrei et al, 2003). Dumstrei et al (Dumstrei et al, 2003) showed that global expression of a dominant-negative form of DE-Cadherin driven by a heat pulse during early second instar results in a severe phenotype that includes deficits in neural proliferation: although neuroblasts appears in approximately normal numbers, they have highly reduced mitotic activity.…”
Section: Research Articlementioning
confidence: 99%
“…Loss of ey function causes overproliferation of neuroblasts and prevents dispersion, leading to large clusters of eypositive neurons. Formation of these large clusters can be rescued by removal of DE-Cadherin (Shotgun -FlyBase), which regulates cell adhesion and neuroblast proliferation (Dumstrei et al, 2003). Thus, eyeless links neurogenesis and migration in the optic lobe, revealing new mechanisms of brain formation in Drosophila that are similar to cortical development in mammals (Ge et al, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…DE-cadherin expression is significantly lower in grh mutant neuroblasts, and Grh-binding sites have been identified in the DE-cadherin flanking sequences (Almeida & Bray 2005). It is thought that DE-cadherin mediates neuroblast-glia interactions that are required for proper neuroblast proliferation (Dumstrei et al 2003). The elucidation of further Grh targets and how these targets might vary in a segment-specific way to control the different behaviours of thoracic and abdominal neuroblasts will be of great interest.…”
Section: (D) Neuroblast Reactivationmentioning
confidence: 99%
“…Drosophila GSCs fulfil this definition because they are totally dependent on direct contact with a niche of specialized cells to the extent that GSCs that abandon their niche lose SC identity and differentiating daughter cells that establish ectopic contact with the niche might acquire SC identity (Brawley and Matunis, 2004;Kai and Spradling, 2004). Indeed, NBs occupy defined anatomical positions during development and are in close contact with neighbouring cells: their most recent daughters on the basal side (Truman and Bate, 1988), and cortex glial cells on their apical and lateral sides (Dumstrei et al, 2003). Moreover, NBs are not insensitive to their neighbours and are definitively responsive to signals like Anachronism or Activin, which are secreted by larval glia (Ebens et al, 1993;Zhu et al, 2008) as well as to Notch, and other signalling pathways that control the number of proliferating NBs in the larval brain (Park et al, 2003;Wang et al, 2006;Lee et al, 2006a).…”
Section: Drosophila Nbs As Sc Modelsmentioning
confidence: 99%